Mapping the public art placemaking process: a case study of Laman Seni, Shah Alam, Malaysia - Azhari, Syamim; Zakariya, Khalilah (Faculty of Applied & Creative Arts, Universiti Malaysia Sarawak (UNIMAS), 2015)
The development of a public market in city planning is pivotal in supporting the growth of the local economy. Markets become assets to the city not only as a platform for informal vendors to conduct businesses but also as a place where the culture of the locals evolves daily. This paper examines Pasar Payang in Terengganu, Malaysia as one of the well-known markets among locals and tourists. The market is located in the city centre, and it will soon go through a redevelopment process. The aim of this paper is to examine the tangible and intangible qualities of the markets that can guide its sustainability in the future. The methods adopted for this study comprises of conducting survey questionnaire among 497 visitors and semi-structured interviews among 19 market vendors. The analysis reveals that the cultural vitality of the market is contributed by its local products and local culture. These two components are dependent on the market vendors, as they are the local people who sell goods at the markets, based on the available local resources and local demands. These findings can contribute to the repositioning of the market as a cultural attraction in sustaining its operation alongside other urban developments.